(untitled) (Revista de Ciências Agroveterinárias, 2014)
The aim of this study was to evaluate the effect of onion cropping systems on microbial carbon and nitrogen from the soil. The study was conducted in a dystrophic Haplumbrept with five treatments consisting of sequences of ground cover crops with the aims of creating a minimum cultivation system, as follows: S1 succession: corn and onion; succession S2: corn, oat / turnip, onion, corn “safrinha” and vetch, corn, rye, onion, R1 rotation: corn, oat / turnip / rye, onion, sunflower, oat / turnip / vetch, beans, rye / radish, onion; rotation R2: onion, millet, turnips, onions, millet, oat / turnip / vetch, corn, barley, onions, rotation R3: onions, beans, pork, rye, onion, velvet beans, rye, onion, velvet beans, rye, onion. Neighboring areas experimented with conventional tillage (CT) and Orchard (PO) and were sampled as reference situations. The evaluations were conducted in 2010, using the following periods: pre-planting (15 days before planting in straw), 15 days after planting and onion bulb training. Soil samples were collected from 0 to 10 cm and the levels of total carbon (TOC), total nitrogen (TN) and carbon and microbial biomass nitrogen (Cmic, Nmic) were determined. The use of plants growing in minimum soil cover allowed highest onion TOC and TN in the soil compared to conventional tillage. The Nmic proved to be the best indicator of changes in conservation and conventional tillage systems. On the other hand, the Cmic did not vary between treatments.